PRIMITIVE IDEALS OF TOEPLITZ ALGEBRA OF ORDERED GROUPS - Rizky Rosjanuardi (IndoMS, 2008)
The topology on primitive ideal space of Toeplitz algebras of totally ordered abelian groups can be identified through the upwards-looking topology if and only if the chain of order ideals is well-ordered. We describe the topology on primitive ideal space of Toeplitz algebra of totally ordered abelian groups when the chain of order ideals is not well ordered.DOI : http://dx.doi.org/10.22342/jims.14.2.55.111-119